2003
DOI: 10.1116/1.1603285
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of resistivity and work function of sputtered-TaN film for gate electrode applications

Abstract: Tantalum nitride (TaN) films were prepared by reactive sputtering in a gas Ar and N2 for gate electrode applications. Resistivity, crystallinity, and work function of the films were investigated as a function of nitrogen flow rate. As the nitrogen flow rate increased from 0 to 20 sccm, the resistivity of as-deposited TaN films increased from 132 to 1.4×105 μΩ cm. With a nitrogen flow rate of 8 and 10 sccm, the fcc TaN phase was obtained. The work function of the TaN films was investigated using TaN-gated nmeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
49
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 8 publications
9
49
0
Order By: Relevance
“…It is also reported that the TaN x,xഛ1 films are sensitive to postprocess oxidation and the O content can result from exposure of the films to the ambient. 39,40 The influence of the plasma exposure time on the film composition was also observed by the change in electrical resistivity of the films as determined by in situ SE ͓Eq. ͑2͔͒ and ex situ four-point probe measurements.…”
Section: -7mentioning
confidence: 99%
“…It is also reported that the TaN x,xഛ1 films are sensitive to postprocess oxidation and the O content can result from exposure of the films to the ambient. 39,40 The influence of the plasma exposure time on the film composition was also observed by the change in electrical resistivity of the films as determined by in situ SE ͓Eq. ͑2͔͒ and ex situ four-point probe measurements.…”
Section: -7mentioning
confidence: 99%
“…[4][5][6] Various barrier, liner and capping layers for Cu interconnects have been reported in the effort to stabilize Cu atoms by suppressing their diffusion and migration, including SiN x , SiCN and transition metal nitrides. [7][8][9] However, when it comes to a 22 nm technology node and below, dimensions of interconnects are already less than the mean free path (MFP) of Cu (~40 nm), while Cu metal conductivity decreases exponentially as it shrinks in size below MFP due to surface and grain boundry scattering. [10][11][12] As a result, by adding several nanometers of a low conductivity tantalum nitride barrier layer (~10 6 S/m) onto Cu (5.96 × 10 7 S/m), the effective width of a Cu wire would be decreased by 10 -20 %, thus drastically decreasing the overall conductivity of the nanoscale interconnects.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18] Traditionally, Co metal was deposited by PVD methods that do not have the capability of coating inside high-aspect-ratio structures. 19 Thus, metal-organic chemical vapor deposition (MOCVD) with cobalt carbonyl precursors [e.g., Co 2 (CO) 8 ] was introduced for better conformality. 20 However, cobalt carbonyl precursors have poor thermal stability and narrow useful deposition temperature windows, and usually lead to a rough film with surface roughness rms higher than 2.2 nm.…”
Section: Introductionmentioning
confidence: 99%
“…These materials have been studied for use in thin-film resistors, wear-resistant coatings on tools, thermal printer heads, gate electrodes, and diffusion barriers in Cu interconnection, which suggest their suitability as diffusion barriers for GaN-based electronics. [38][39][40][41] Selected properties of these materials are given in Table I. In this paper, we report results on Ohmic contacts based on these materials to n-GaN.…”
Section: Introductionmentioning
confidence: 99%